Type-2 fuzzy reaching law speed control of an electric drive - Akpolat, Z.H.; Altinors, A. (Acta Press, 2007)
In this paper, a new control scheme is described for the robust speed control of electrical drives. The proposed control method is based on type-2 fuzzy logic and Sliding Mode Control (SMC) technique. In the design of the proposed controller, Reaching Law Control (RLC) approach - a SMC design method-is used. Takagi-Sugeno-Kang (TSK) fuzzy system and interval type-2 fuzzy sets are preferred due to their suitability for control applications, Non-singleton fuzzification is employed because of its effectiveness on uncertainties. The control performance is tested under inertialfrictional variations and external load torque disturbances. To show the effectiveness of the new control approach, simulation results of the SMC and type-2 fuzzy SMC (T2FSMC) systems are presented together.
Keywords: Drive control; Reaching law control; Robust control; Sliding mode control; Speed control; Type-2 fuzzy logic